Answer:
a = - 5.
Step-by-step explanation:
The given equation is,
We need to change it to its numerical form ⟶ - (5 - (a + 1)) = 9 - (5 - (2a - 3))
Now, by solving it...
[tex]-(5-(a+1))=9-(5-(2a-3))\\-\left(5-a-1\right)=9-\left(5-\left(2a-3\right)\right) \\-\left(4-a\right)=9-\left(5-\left(2a-3\right)\right) \\-4+a=9-\left(5-\left(2a-3\right)\right) \\-4+a=9-\left(5-2a-\left(-3\right)\right) \\-4+a=9-\left(5-2a+3\right) \\-4+a=9-\left(8-2a\right) \\-4+a=9-8-\left(-2a\right) \\-4+a=9-8+2a \\-4+a=1+2a \\-4+a-2a=1 \\-4-a=1 \\-a=1+4 \\-a=5 \\\boxed{a=-5 }[/tex]
__________
Hope it helps!
[tex]\mathfrak{Lucazz}[/tex]